Pentecostalism and the Yoruba World View: The case of Mountain of Fire and Miracles Ministries, Nigeria - Omotoye, Rotimi Williams (The international journal of religion and spirituality in society, 2011)
Pentecostalism is the latest brand of Christianity in Nigeria. It became popular in the last four decades. Our focus in this study is the Mountain of Fire and Miracles Ministries founded by Pastor (Dr) Daniel Olukoya in 1981 in Lagos. The Church has introduced a new dimension to the understanding of Christianity in Nigeria and beyond. The focus of the Church is deeply rooted in African cosmology of evil, magic and witchcraft. These phenomena have attracted both Christians and non-Christians to the church. It is believed that the malevolent forces are responsible for sicknesses, misfortunes, untimely death, poverty and oppression. Within few years of its existence, branches of the church are found in many states of the country and countries like Ghana, United States of America, United Kingdom and the Scandinavian countries. Our concern in this study is to examine critically the reasons for the phenomenal growth of the church.